An evaluation of the MEDLINE database of U.P. Manila Medical Library its coverage and usage - Delgado, Emelorna C. Esteban; Faderon, Rosalie B.; Rosal, Rosvida R. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
MEDLINE has long been appreciated as a major resource for those with academic or research questions. More recently, it has been recognized that MEDLINE supports informed clinical practice as well. A number of published studies report that MEDLINE literature searches have a significant positive effect on clinical problem-solving and patient outcomes.
This study primarily assessed the MEDLINE database, its coverage of periodical titles and its usage in the Medical Library UP Manila. The objectives of this study were to: 1. Evaluate the MEDLINE database based on the following criteria: consistency, coverage/scope, accuracy, output, customer's support and training, accessibility/ease of use, timeliness; 2. Determine the UPM College of Medicine practitioner's areas of specialization that are covered by the MEDLINE database; 3. Identify the medical journal titles in MEDLINE database that were most heavily used for the school year 2003-2004; 4. Determine if the users use databases other than MEDLINE; 5. Determine methods of delivery (electronic mail and online display) and delivery formats in accessing journals in MEDLINE database; and 6. Come up with recommendations regarding the MEDLINE database. The 785 medical practitioners of 27 departments of the University of the Philippines-Philippine General Hospital as of June 2003 to March 2004 comprised the respondents of this study. The descriptive method of research was used. The data from the statistics of use of the library users of UP Medical Library from June 2003 to March 2004 were used and consulted (the descriptive document usage delivery method and the document usage by journal using MEDLINE database through ProQuest) for additional data needed in the study. The data gathered were organized and tabulated, tallied, analyzed and interpreted using percentages and ranking.
The findings of the study proved that MEDLINE database is useful in retrieving information in the areas of specialization of UP Manila College of Medicine practitioners. The availability of online databases affects internal library use, particularly when databases can be accessed through the Internet. Librarians at the UP Medical Library must endeavor to keep abreast of the range of options that are available to them and their users, and should be well-equipped to evaluate those options effectively. Using the SCOUG criteria as a guide when examining different versions of the same database, librarians and other information professionals should be able to make an informed assessment of the relative value and usefulness of a range of services of databases. The UP Medical Library does not need to subscribe to the MEDLINE software since it is available for free from the Internet. If there are funds allotted for the subscription of the said software, it is better to divert the funds to other library expenses. Users of the MEDLINE and other medical databases are encouraged to access the electronic journals. Since full-text versions of many medical journals are being offered via the Internet, it will be increasingly easier to locate the original papers, which will be linked to the results of the user's search. A user should be aware that MEDLINE does not cover all the medical literature in the world. Users are advised to use other databases like EMBASE, MD Consult, Ovid MEDLINE, and other to cover a wider collection of the world's medical literature.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: MEDLINE; Medical literature -- Databases -- Evaluation